Resilience of the larval slipper limpet Crepidula onyx to direct and indirect-diet effects of ocean acidification - Maboloc, Elizaldy A. (Sci Rep, 2017)
Ocean acidification (OA) is known to directly impact larval physiology and development of many marine organisms. OA also affects the nutritional quality and palatability of algae, which are principal food sources for many types of planktonic larvae. This potential indirect effect of OA via trophic interactions, however, has not been fully explored. In this study, veligers of Crepidula onyx were exposed to different pH levels representing the ambient (as control) and low pH values (pH 7.7 and pH 7.3) for 14 days, and were fed with Isochrysis galbana cultured at these three respective pHs. pH, diet, nor their interactions had no effect on larval mortality. Decrease in pH alone had a significant effect on growth rate and shell size. Structural changes (increased porosity) in larval shells were also observed in the low pH treatments. Interactions between acidification and reduced diet quality promoted earlier settlement. Unlike other calcifying molluscs, this population of slipper limpets introduced to Hong Kong in 1960s appeared to be resilient to OA and decreased algal nutritional value. If this robustness observed in the laboratory applies to the field, competition with native invertebrates may intensify and this non-native snail could flourish in acidified coastal ecosystems.